2017
DOI: 10.1088/1361-6463/aa8e2b
|View full text |Cite
|
Sign up to set email alerts
|

Developmental switching inPhysarum polycephalum: Petri net analysis of single cell trajectories of gene expression indicates responsiveness and genetic plasticity of the Waddington quasipotential landscape

Abstract: The developmental switch to sporulation in Physarum polycephalum is a phytochrome-mediated far-red light-induced cell fate decision that synchronously encompasses the entire multinucleate plasmodial cell and is associated with extensive reprogramming of the transcriptome. By repeatedly taking samples of single cells after delivery of a light stimulus pulse, we analysed differential gene expression in two mutant strains and in a heterokaryon of the two strains all of which display a different propensity for mak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 74 publications
(103 reference statements)
0
18
0
Order By: Relevance
“…In previous studies we have shown that the gene expression pattern in samples taken at the same time from different sites of a plasmodium covering a standard Petri dish (9 cm Ø) did not change within the limits of accuracy of the measurements. Accordingly, repeated sampling of the same plasmodial cell yields true time series ( Rätzel, 2015 ; Werthmann and Marwan, 2017 ). To allow more samples to be taken without consuming too much of the plasmodial mass, we now prepared plasmodia on 14 cm Ø Petri dishes, increasing the surface area covered by the plasmodial mass by 2.4-fold, and took smaller samples by punching agar plugs of 1.13 cm 2 per sample, to harvest a small portion of the initial total plasmodial mass.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies we have shown that the gene expression pattern in samples taken at the same time from different sites of a plasmodium covering a standard Petri dish (9 cm Ø) did not change within the limits of accuracy of the measurements. Accordingly, repeated sampling of the same plasmodial cell yields true time series ( Rätzel, 2015 ; Werthmann and Marwan, 2017 ). To allow more samples to be taken without consuming too much of the plasmodial mass, we now prepared plasmodia on 14 cm Ø Petri dishes, increasing the surface area covered by the plasmodial mass by 2.4-fold, and took smaller samples by punching agar plugs of 1.13 cm 2 per sample, to harvest a small portion of the initial total plasmodial mass.…”
Section: Resultsmentioning
confidence: 99%
“…The temporal sequences of gene expression patterns classified as Simprof significant clusters defined a trajectory for each individual cell and revealed significant differences between cell trajectories ( Table 2 ). To relate gene expression states and trajectories we constructed a Petri net (bipartite graph) as previously described ( Werthmann and Marwan, 2017 ; Rätzel et al, 2020 ), by representing each gene expression state by a place and the temporal transit between two states by a transition ( Figure 5 ). A single token marking one place of the Petri net indicates the current gene expression state of a cell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 36 ] PN is very appropriate for the quantitative and qualitative modeling of concurrent, asynchronous and distributed systems and widely used for modeling of biological networks. [ 39 40 41 42 43 44 ] Steggles et al introduced a method for automatic translation of BN into PN model. [ 45 ] Zhang et al created a stochastic model of BYCC and defined 2048 cell states whose transition probabilities between these states are affected by noise parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The true slime mold Physarum polycephalum is a well known model organism [8] that exhibits mechano-chemical spatio-temporal patterns. Previous research in Physarum has addressed many different topics in biophysics, such as genetic activity [9], habituation [10], decision making [11] and cell locomotion [12, 13]. Physarum is an unicellular organism, which builds large networks that exhibit self-organized synchronized contraction patterns [8, 14, 15].…”
Section: Introductionmentioning
confidence: 99%